DIRECT THERMOELECTRIC MICROGENERATION USING RESIDUAL HEAT OF PHOTOVOLTAIC SYSTEM - Camargo, José Rui; Silva, Jalmir Machado; Godoy Junior, Ederaldo (Revista Ciências Exatas, 2023)
All photovoltaic panel heats up when exposed to sunlight and this heating reduces the electrical power output of the same. This work presents the use of this unwanted waste heat, converting it into thermal energy directly by means of the Seebeck effect, which is the direct conversion of thermal energy into electrical energy by means of an arrangement of semiconductor materials that when exposed to temperature gradients generate electric current. In this work emphasis was placed on the influence of temperature on generation processes involved. Thus, the theoretical evaluation, it presents the mathematical models of thermoelectric and photovoltaic systems by raising the curves of voltage, current and electric power generated, and analyses the influence of temperature in each model. To obtain the simulation curves it uses MATLAB ® 5.3, taking into account the parameters of thermoelectric modules and real photovoltaic cells. In practical evaluation, a prototype was assembled containing thermoelectric module attached to the bottom of a photovoltaic panel in order to use the heat energy absorbed by the panel. The data were stored and analyzed, where we observed the influence of temperature in both systems, validating the mathematical modeling. It is the applicability of the mathematical model given the results obtained with the prototype system.